SYMBOLIC CONVERGENCE IN ALFIN RIZAL'S INSTAGRAM POETRY - Mawaidi; Suminto A. Sayuti; Wiyatmi (Literature and Literacy, 2024)
Literary works such as poetry are no longer limited to books. In the digital age, poetry has also shifted to media that easily accessible by readers. It means that poetry is no longer consumed by specific community only. Poetry can be consumed by people from various demographics; age and gender; and can be expressed by anyone from various backgrounds through social media platforms such as Instagram. This study discussed Instagram poetry from the theoretical perspective of symbolic convergence. The data sources for this research were the poems of Alfin Rizal, analyzed qualitatively. Data was collected from the Instagram account @alfinrizalisme, supported by Alfin Rizal's poetry books. Each piece of poetry content on Alfin Rizal's Instagram was classified into smaller taxonomies to facilitate findings. The findings of this study indicated the dramatization of messages by Alfin Rizal, which impacts public response to his work. This message dramatization takes the form of poetry videos, photo manipulation, background as the setting, and illustrations as a secondary backdrop. Another finding was the construction of symbolic reality, which affects public interaction (followers) who utilize this message dramatization (in the form of Instagram posts with poetry content) to re-communicate to the public through other social media platforms.